A Review and Analysis of MAODV routing protocols for Mobile Ad Hoc Networks - Babu, D. Madhu; Ussenaiah, M (International Journal of Computer Sciences and Engineering, 2025)
Mobile Ad hoc Networks have gained significant interest and popularity due to their open architecture, capability of changing location and self-configuring as per the needs and requirements of the users. The expanding ubiquity and accessibility of portable remote gadgets has lead analysts to build up an assortment of Mobile Ad hoc Networking (MANET) Protocols. This paper presents study of various sorts of Multicast Ad hoc On-Demand Vector (MAODV) directing protocols which offers fast adjustment to dynamic link conditions, low handling and memory overheads. Multicasting sends the information to a group of host PCs by utilizing single source address. The main objective of multicasting is to support group-oriented computing, which can reduce communication costs, processing overheads and delivery delay. Finally this paper analyses various MADOV routing protocols according to particular attributes which enables to reveal the significance of the research work went on in MAODV routing protocol and summarized literature reviews and its findings are presented in tabular form.